MODERN VIEW ON THE ANALYSIS OF TRANSFORMATION OF THE CONCEPT OF GENDER TOLERANCE IN CIVILIZATION AND CULTURE OF THE WEST AND EAST. SOCIAL AND PHILOSOPHICAL ASPECT (Web of Teachers: Inderscience Research, 2024)
The article analyzes the philosophical and social aspect of gender in the civilization and cultural life of the West and East, issues of gender equality, the rights of men and women. This transformation is reflected in the development trend of civilization of the West and East, scientific, educational, social and philosophical worldview. The features of Western and Eastern gender history, gender relations, the role of gender equality issues.